2001
DOI: 10.1080/01062301.2001.10592610
|View full text |Cite
|
Sign up to set email alerts
|

Attachment theory and psychoanalysis: controversial issues

Abstract: On the present theoretical arena of psychoanalysis, attachment theory has obtained increasing attention, especially from psychoanalysts interested in empirical research. This paper presents the controversies raised by Bowlby's theory, and discusses the relationship between attachment theory and psychoanalysis. Although Freud and Bowlby differ in their image of Man, ideas developed within attachment theory have parallels in those of psychoanalytic object relation theories, both with regard to the conceptualisat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
4

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 15 publications
0
5
0
4
Order By: Relevance
“…The infant is perceived from an interactional perspective, with a focus on the relationships with primary attachment figures. Attachment theory maintained some foundations of psychoanalytic theory (e.g., the developmental point of view) and there is a strong literature that discusses the divergences and convergences of psychoanalysis and attachment theory (e.g., Diamond and Blatt, 1999 ; Fonagy, 1999 , 2001 ; Slade, 2000 ; Gullestad, 2001 ; Steele and Steele, 2008 ; Eagle, 2013 ) and also developed some aspects further, particularly the delineation of the internal world ( Diamond and Blatt, 1999 ). Fonagy’s (1999 , 2001 ) overview of the intersection of these two approaches demonstrated that the relationship between attachment theory and psychoanalysis is more complex than adherents of either community have generally recognized.…”
Section: Introductionmentioning
confidence: 99%
“…The infant is perceived from an interactional perspective, with a focus on the relationships with primary attachment figures. Attachment theory maintained some foundations of psychoanalytic theory (e.g., the developmental point of view) and there is a strong literature that discusses the divergences and convergences of psychoanalysis and attachment theory (e.g., Diamond and Blatt, 1999 ; Fonagy, 1999 , 2001 ; Slade, 2000 ; Gullestad, 2001 ; Steele and Steele, 2008 ; Eagle, 2013 ) and also developed some aspects further, particularly the delineation of the internal world ( Diamond and Blatt, 1999 ). Fonagy’s (1999 , 2001 ) overview of the intersection of these two approaches demonstrated that the relationship between attachment theory and psychoanalysis is more complex than adherents of either community have generally recognized.…”
Section: Introductionmentioning
confidence: 99%
“…When submitting new theories we should not violate the principle of parsimony in science by offering hypotheses which in contrast to existing theory becloud the observational facts, are oversimplifi ed, and make no contribution to the better understanding of observed phenomena. (1960, p. 94) Thirty-fi ve years later, Köhler diagnosed an 'incompatibility [of the] conceptual frameworks' of attachment theory and psychoanalysis (1995, p. 71; see also Gullestad, 2001). From an epistemological viewpoint, human behaviour is explained tautologically and is made a mere manifestation of an abstract idea implanted in biology.…”
Section: Discussionmentioning
confidence: 99%
“…Diese aus mehreren, von unabhängigen Auswertern ermittelten Forschungsbefunde korrespondieren mit dem Eindruck der Therapeutin, die Patientin habe "eine innere Sicherheit (…) aufbauen können" und einen "inneren Reichtum" entwickelt. Inwieweit die Konzepte der Bindungsforschung aber tatsächlich in die behandlungstechnischen Überlegungen der untersuchten Therapeutin einflossen, kann mithilfe der Ergebnisse aus dem AAI und dem AAP nicht belegt werden [46].…”
Section: Diskussion ▼unclassified